Peran Gender, Pendapatan, dan Pendidikan Terhadap Loyalitas Konsumen Yang Berkunjung ke Mall - Haryono, Tulus; Hastjarjo KB, Dwi (KINERJA, 2010)
This Ã‚Â study Ã‚Â was Ã‚Â meant Ã‚Â to Ã‚Â explain Ã‚Â the Ã‚Â relation Ã‚Â between Ã‚Â relationship marketing, Ã‚Â consumer Ã‚Â trust,Ã‚Â consumer commitment, and consumer loyalty moderated by gender, income, and education. TheÃ‚Â data were collected through surveys to consumers loyal to Malls.Ã‚Â Based on the number of the sample, the tests of sample validity and reliability showed that theÃ‚Â result Ã‚Â was Ã‚Â that Ã‚Â the sample Ã‚Â was Ã‚Â valid Ã‚Â and Ã‚Â reliable. The Ã‚Â data Ã‚Â analysis Ã‚Â was Ã‚Â carried Ã‚Â out Ã‚Â by usingÃ‚Â Ã¢â‚¬Å“Structural Equation ModelÃ¢â‚¬Â (SEM).Ã‚Â The Ã‚Â findings Ã‚Â of Ã‚Â the Ã‚Â present Ã‚Â study shows Ã‚Â that: Ã‚Â (1) Ã‚Â there Ã‚Â is Ã‚Â a Ã‚Â positive Ã‚Â and Ã‚Â significant Ã‚Â relationÃ‚Â between relationship Ã‚Â marketing Ã‚Â and Ã‚Â  Ã‚Â consumer Ã‚Â trust, Ã‚Â (2) Ã‚Â there Ã‚Â is Ã‚Â a Ã‚Â positive Ã‚Â and Ã‚Â no significantÃ‚Â relation between relationship marketing and consumer commitment, (3) there is a positive andÃ‚Â significant Ã‚Â relation Ã‚Â between Ã‚Â consumer Ã‚Â trust Ã‚Â and consumer Ã‚Â commitment, Ã‚Â (4) Ã‚Â there Ã‚Â is Ã‚Â a Ã‚Â positiveÃ‚Â and significant relation between consumer commitment and consumer loyalty, and (5) there is aÃ‚Â positive and no significant relation between relationship marketing and consumer loyalty.